When we see you again - Goldberg-Polin, Rachel, 1969- (Random House, 2026)
A searing portrait of a mother's grief and strength in the wake of unthinkable tragedy. Once upon a time, I was meandering down the road of life with my husband, Jon. It was a regular and beige life, and it worked. It was a warm beige. We felt, and were, blessed and lucky. Normal. On the morning of October 7th, 2023, Rachel Goldberg-Polin's beloved twenty-three-year-old son, Hersh, was stolen from a music festival billed as a celebration of unity and love--and, in that moment, her life was forever separated into The Before and The After. Over the next eleven months, she and her husband, Jon, would work tirelessly--in public and behind the scenes--to secure the hostages' release, to breathe some humanity into the situation while they were experiencing relentless emotional and psychological torment. The power of her raw and fervent pleas soon made her the face of the hostage crisis. And when Hersh and five other captives were executed after surviving 328 days of violence and cruelty, she would also become the face of its ultimate cost. In When We See You Again, Rachel pours her pain, love, and longing onto paper, giving voice to the broken among us, and reminding us that even when the world feels choked with darkness, light exists in a different way. How do we find it? Her own experience has been extreme, but at its essence, this is a universal story of trying to live with grief. It is a story of how we remember and how we persevere, of how we suffer and how we love. "There are days when I break completely," she writes. "I have cried for an entire day straight. I didn't think it was physically possible, but the weeping never let up. That is a very long time to cry. I kept hoping I would run out of tears. And then there are days when there is a whisper of sun. Not out there in the sky. In me. In us."--